Infectivity and viability of dengue virus infected hepatocytes cocultured with peripheral blood mononuclear cells from a healthy subject (Medical Journal of Indonesia, 2020)
BACKGROUND Dengue virus (DENV) can infect and replicate in monocytes, resulting in antibody-dependent enhancement. The liver is the main target of DENV, and the infection mechanisms of DENV include direct cytopathic effects (CPEs) of the virus, mitochondrial dysfunction, and effect of cellular and humoral immune factors in the liver. This study was aimed to explore the infectivity of DENV and viability of human hepatocytes using Huh 7it-1 cells cocultured with peripheral blood mononuclear cells (PBMCs). METHODS Huh 7it-1 cells were infected with dengue virus serotype-2 (DENV-2) New Guinea C strain at multiplicity of infection of 0.5 and 1 FFU/cell, and cocultured in vitro with and without adherent PBMCs. The infectivity of DENV was assessed by immunoperoxidase staining. The viability of Huh 7it-1 cells was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT, a tetrazole) assay and trypan blue staining. Data were statistically analyzed by ShapiroWilk and analysis of variance for normality significances. RESULTS The result showed that addition of PBMCs to DENV-2 infected Huh 7it-1 cells decreased the infectivity of DENV (1537%). DENV-2 infection decreased the viability of Huh 7it-1 cells (15.520.8%). Despite the decrease in infectivity of DENV, the addition of PBMCs increased the Huh 7it-1 cells viability (4.510.2%). CONCLUSIONS Addition of PBMCs to Huh 7it-1 cells that are infected with DENV-2 decreased the infectivity of DENV and increased Huh 7it-1 cells viability.